Uso de acupuntura y moxibustión en el manejo de parálisis cerebral tetraparésica discinética : reporte de un caso clínico - Vieira, Marco (2016)
a b s t r a c t This article presents a case study of an 11-year-old boy with tetraparetic dyskinetic cerebral palsy that was treated with acupuncture and moxibustion, along with conventional therapy in a hospital. The objective to verify how acupuncture/moxibustion can be advantageous in treating patients with cerebral palsy. Continuous treatment with acupuncture and moxibustion was provided over 3 months. There was significant progressive improvement in their clinical picture, which suggests that acupuncture and moxibustion can be an effective combination as adjuvant treatment for tetraparetic dyskinetic cerebral palsy.